How to use visual methods to promote health among adolescents: A qualitative study of school nursing. Issue 13 (17th April 2019) - Laholt, Hilde; Guillemin, Marilys; McLeod, Kim; Beddari, Ellinor; Lorem, Geir
Abstract: Aims and objectives: Public health nurses attended a 3‐day course to learn the use of visual methods in health dialogue with adolescents. The aim of this study was to explore how to use visual methods to promote health among adolescents in a school nursing context. Background: Photovoice is a visualising technique that enables adolescents to participate in health promotion projects in a school setting. Photovoice also enhances work of public health nurses and other health professionals. Design: This was a qualitative action research study. We developed and conducted a course in visual methods and used data from focus group discussions in combination with participant observations involving public health nurses working in school health services. Methods: We conducted focus group interviews ( n  = 40) using separate semi‐structured discussion guides before and after a course in visual methods. The interviews were audio recorded and transcribed verbatim, and we documented the workshops ( n  = 8) through field notes. We collected the data from January–October 2016. Data were analysed and coded into themes and subthemes using systematic text condensation. We reported the study in accordance with the COREQ checklist. Findings: Public health nurses found photovoice useful in school nursing. The use of images offered pupils an active role in dialogues and more control in defining the topics and presenting their stories. When nurses allowed adolescents to bring images into conversations, they discovered new insights into public health promotion. The public health nurses pointed out the benefits and challenges of using new methods in practice. Conclusion: Public health nurses considered photovoice to be useful in health promotion and other public health issues. Involving pupils in bringing images to conversations offered them an active role and voice in health promotion. Relevance to clinical practice: We recommend the use of photovoice and visual technologies (e.g., smartphones) in health promotion activities for adolescents.